Analisis Peran Pendidikan Kewarganegaraan Dalam Implementasi Kurikulum Merdeka Di Sma Negeri 1 Hiliduho - James Hendrafor Gea; Paskalis Gulo; Andika Taufik Perdamaian Telaumbanua (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the role of Citizenship Education (PKn) in supporting the implementation of the Independent Curriculum at SMA Negeri 1 Hiliduho. The Independent Curriculum emphasizes student-centered learning, character building, and the formation of Pancasila student profiles. PKn, as a subject that functions to form intelligent, active, and responsible citizens, is an important component in achieving these goals. Through a descriptive qualitative approach, data were collected through in-depth interviews, learning observations, and documentation studies. The results of the study indicate that PKn has a significant contribution to the formation of student character, increasing democratic literacy, and strengthening attitudes of tolerance and social responsibility. However, its implementation still faces challenges such as limited contextual teaching materials, lack of teacher training, and low student involvement in the participatory learning process.